NK4 Regulates Laryngeal Squamous Cell Carcinoma Cell Properties and Inhibits Tumorigenicity by Modulating the DKK1/Wnt/β-Catenin Axis - Zhang, Shoukai; Wei, Hulai; Ha, Xiaoqin; Zhang, Yueyu; Guo, Yufen (Frontiers in Oncology, 2021)
Objective: To investigate the effects of NK4 gene on the proliferation, migration, apoptosis, cell cycle of AMC-HN-8 laryngeal carcinoma cells and tumor formation in nude mice and related mechanisms.Methods: The attenuated Salmonella carrying the NK4 gene was used to transfect the AMC-HN-8 cells, and the qRT-PCR was used to detect the expression of NK4 in the AMC-HN-8 cells. The effects of NK4 gene on the proliferation, migration, apoptosis and cell cycle of laryngeal carcinoma AMC-HN-8 cells were detected by MTT method, cell scratch test, and flow cytometry. A nude mouse tumorigenesis model was used to evaluate the effect of NK4 gene on the growth of AMC-HN-8 cells in vivo. Western blot method was used to detect the expression of DKK1, Wnt and β-Catenin in transplanted tumor tissues and control tissues. Results: The results of qRT-PCR showed that the expression of NK4 in the transfection group was significantly higher than that in the control group (P<0.01). MTT results showed that high expression of NK4 would inhibit the proliferation of AMC-HN-8 cells (P<0.01). The results of the scratch experiment showed that with the increase of transfection time, the healing rate of cell scratches was lower than that of the control group, and the cell migration ability decreased (P<0.01). The results of AnnexinV/PI double staining experiment showed that NK4 gene induced an increase in AMC-HN-8 cell apoptosis (P<0.01). The subcutaneous tumor formation experiment in nude mice proved that the tumor formation ability of AMC-HN-8 cells was weakened after the high expression of NK4 (P <0.05). WB detection showed that the expression of DKK1, Wnt1, and β-Catenin protein decreased after the high expression of NK4. Conclusion: NK4 gene can inhibit the proliferation and migration of laryngeal carcinoma AMC-HN-8 cells, promote cell apoptosis, and induce cell cycle arrest in S phase. The high expression of NK4 can inhibit the tumorigenesis ability of AMC-HN-8 cells, which may be related to the regulation of DKK1/Wnt/β-Catenin signal axis.